Modelling study of magnetic and concentration phase transition in ultrathin antiferromagnetic films - Leonid, Afremov; Aleksandr, Petrov (Journal of physics. Conference series, 2014)
Using the method of the "average spin" a modelling study of magnetic and concentration phase transition in ultrathin antiferromagnetic of different crystalline structure has been carried out. It has been shown, that relative change of Neel temperature is subject to the power law with negative index which doesn't depend on the film's crystal kind. The calculation of the dependence of phase transition critical concentration in diluted magnetic material on the film thickness has been made out. The legitimacy of the use of the method developed for modelling of magnetic and concentration phase transition in different nanostructures is certified by accordance between the results of calculations and the experimental data.